TALIBAN I AFGHANISTAN - Olesen, Asta (Tidsskriftet Antropologi, 1998)
Asta Olesen: Taliban in Afghanistan In October 1994 the Taliban religious militia emerged as a new force on the Afghan war scene, and during the following three years they have brought more than 2/3 of the country under their control. The Taliban, originating from the religious schools of NWFP of Pakistan, brought relative peace to the areas under their control, but through their victory over the competing mujahedin commanders they also gave birth to one of the most religiously conservative regimes in the world. In spite of denying women any role in public life, closing giris’ schools, banning music, TV and photography in general, punishing men for trimming their beards, the Taliban’s success to a large extent depends on their relatively high support among the population. The explanation shall be sought in their ethnic/tribal origin, their extreme puritanism which originated in the tribal code of the Pashtuns rather than in Islam - and in the anarchy which has reigned in Afghanistan, particularly after the fail of the pro-communist PDPA regime in 1992. The article concludes that the Taliban success contains the seeds of its eventual failure.